Visualization Tools for Executive-Level Information Management Reporting - Obidhusin, Saef; Rajesh, Deepa; Jawabri, Adnan; Prabakaran, N.; Ibragimov, A’lamjon; Kaur Chhabda, Parvindar (Indian Journal of Information Sources and Services, 2025)
Today's enterprises operate within a highly competitive context, necessitating multifaceted data processing frameworks for informed executive decision-making through a paradigm of data visualization. Reporting tools that provide both insights and aesthetic appeal are benefiting businesses. This paper analyses a case study focused on business intelligence tools, specifically Power BI, Tableau, and Google Data Studio, and examines their significance in management reporting at the executive level. The tools under study enable the visualization of KPIs and facilitate the analysis of performance trends, thereby improving information-driven and decision-making operational outcomes. The tools simplify and enhance communication by providing real-time, accurate data, thus enhancing organizational transparency and data stewardship. The advanced planning capabilities of these platforms are further improved through Artificial Intelligence (AI) and Machine Learning (ML) technologies, which enhance predictive functions. Moreover, this document considers other discussed criteria, such as tool appropriateness in terms of scalability, system customizability, and user-friendly access. Data privacy concerns, the absence of skilled personnel, and maintaining an accurate set of data also pose challenges, which are discussed further in the document. Evidence gathered supports the statement that advanced organizational goals, when aligned with appropriate visual constructs, enhance the efficacy of executive reporting. AI has rapidly expanded mobile reporting, providing immediate access to information visualization, indicating a direction for future trends. Consequently, for enterprises seeking to remain agile and competitive in a rapidly growing market, adopting sophisticated visualization tools is no longer an option; it is, rather, a prerequisite.